2012
DOI: 10.1261/rna.034934.112
|View full text |Cite
|
Sign up to set email alerts
|

Association of Argonaute proteins and microRNAs can occur after cell lysis

Abstract: MicroRNA (miRNA) target identification is a challenging but important endeavor. Global analyses of the direct mRNA targets of miRNAs have relied heavily upon immunopurification techniques, wherein a core protein component of the miRNA-protein complex, Argonaute (Ago), is immunoprecipitated to isolate associated RNAs. This approach involves the assumption that the selected RNAs were bound to the Ago protein in vivo and that the methodology did not significantly perturb endogenous interactions or produce novel i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 35 publications
0
63
0
2
Order By: Relevance
“…This presents a problem because most applications of in vivo SHAPE require measurement of RNA structure in live, healthy cells. Several recent reports have demonstrated that after cell lysis, RNA molecules can reassociate with trans-acting RNAs and proteins (Mili and Steitz 2004;Riley et al 2012;Riley and Steitz 2013), which would likely alter the RNA structures of such RNAs. Such reasons underscore the concern that 1M7 may be preferentially modifying RNAs in nonnative contexts.…”
Section: Resultsmentioning
confidence: 99%
“…This presents a problem because most applications of in vivo SHAPE require measurement of RNA structure in live, healthy cells. Several recent reports have demonstrated that after cell lysis, RNA molecules can reassociate with trans-acting RNAs and proteins (Mili and Steitz 2004;Riley et al 2012;Riley and Steitz 2013), which would likely alter the RNA structures of such RNAs. Such reasons underscore the concern that 1M7 may be preferentially modifying RNAs in nonnative contexts.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, though the presence of TFIIIA-9ZF in the nucleoplasm is negligible as assessed by confocal microscopy ( Figure 5), we cannot rule out that a small amount of TFIIIA-9ZF interacted with Pol II. A more reasonable explanation is that TFIIIA-9ZF interacts with Pol II post-cell lysis, which has been observed in the interactions between Argonaute proteins and small RNAs (Riley et al, 2012). These two possibilities await clarification by future experiments.…”
Section: Pol II Interacts With Tfiiia Variantsmentioning
confidence: 88%
“…17). However, there were several drawbacks, including the potential for the association of RNA and RNA-binding proteins to occur post-lysis (18) and the failure of these techniques to identify the precise site of targeting. An important methodological advance was the covalent cross-linking of closely juxtaposed RNA and protein by UV irradiation [cross-linked immunoprecipitation (CLIP)-based methodologies].…”
Section: Identification Of Mirna Targets On a Transcriptome-wide Scalementioning
confidence: 99%